The Analysis of Factors Affecting Hemoglobin Levels in Pregnant Women - Retno Palupi Yonni Siwi (Institute of Computer Science (IOCS), 2021)
Anemia is a condition of lack of hemoglobin (Hb) levels in the blood caused by a lack of intake of nutrients needed in the process of forming hemoglobin. Anemia in general occurs throughout the world, especially in developing countries. In developing countries, anemia occurs in women by 45% while in developed countries it is 13%. red blood cells (erythrocytes). The design of this research is Literature Review . A literature review study is a method used to collect data or sources related to a particular topic that can be obtained from various sources such as journals, books, internet and other references. By analyzing the factors that affect hemoglobin levels in pregnant women is the ideal age in pregnancy is 20-35 year, Chronic Energy Deficiency/Kurang Energi kronis (KEK), 41% (2.0 million) pregnant women suffer from malnutrition. Infectious Diseases Pregnant women are very sensitive to infections and infectious diseases,Pregnancy distance of less than 2 years shows a higher proportion of maternal deaths. The education experienced by a person has an influence on increasing thinking skills and knowledge. Compliance of pregnant women is seen from mothers who consume 10 Fe tablets in each month of her pregnancy. Based on the description above, the analysis of the factors that affect hemoglobin levels in pregnant women concludes because: mother's age, Chronic Energy Deficiency (CED), Infectious Diseases, Pregnancy Distance, Education and Knowledge